SISTEM KONTROL SUDUT PITCH BILAH TURBIN ANGIN MENGGUNAKAN LOGIKA FUZZY UNTUK VARIABLE SPEED VERTICAL AXIS WIND TURBINE (VAWT) - Hidayat, Mohammad Noor; Hasanuddin; Wibowo, Sapto (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2022)
VAWT (Vertical Axis Wind Turbine) is a turbine that has an upright mechanical structure with its blades rotating toward a perpendicular z-axis. Based on the experimental results, it is found that there is a relationship between the rotational speed of turbine that rotates generator with the output voltage and power. Thus, it is necessary to control the wind turbine speed so it can rotate according to the set point to be achieved. The contribution of this research is the development of a Fuzzy logic-based control system to control the speed of VAWT turbine where the speed of turbine is used as feedback. To design a Fuzzy rule base, the characteristics of the wind turbine’s response to wind speed are investigated first. Then Fuzzy logic-based controller is created and implemented. To test the effectiveness of the Fuzzy controller made, the implementation is carried out on a VAWT turbine while the simulation is applied to PMSG model using wind turbine through Simulink/Matlab. Based on simulation and experiment results, the performance of the control system using Integral Absolute Error (IAE) for each turbine speed set point value (35, 45, 85, and 100 RPM), it is found that for a small set point value, the IAE value will be larger than higher setpoints. The percentage of the average IAE value for the simulation is 10.25% higher than the experiment. It further shows that the control turbine speed at low speeds is relatively more difficult than at higher speeds.